Health Insurance Literacy and Medical Care Avoidance Among International Students: A Case Study - Echu Liu; Samantha A. Arledge; Miao Cai; Donghua Tao; Wei Li (Frontiers Media S.A., 2023)
Objectives: This research examines the health insurance literacy and healthcare utilization of international students attending a university in the US Midwest.Methods: One hundred and forty-three undergraduate and graduate students attending a midsize metropolitan university in the Midwest completed an online survey in early 2022.Results: Many students surveyed could not identify the definitions of basic terms, such as copay. Furthermore, about 80% of students surveyed could not determine their financial responsibilities in two medical settings. Regression results show that the continent they are from and the length of their stay in the United States significantly predict their understanding of key health insurance terms. More than half of the international students surveyed indicated they often feel confused about their health insurance (57.34%). Only about 20% have delayed or skipped care due to unfamiliarity with the health insurance system.Conclusion: The health insurance literacy of most international students at the midwestern university we surveyed is not ideal. This and possibly other universities in the United States should take more initiatives to help their international students understand the health insurance system.